Analisis indeks morfometrik kerbau rawa betina usia 12 – 18 bulan di desa bantarpanjang, kecamatan cibingbin, kabupaten kuningan - Fauzan Aditya Putra Suherman; Johar Arifin; Raden Siti Darodjah (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
This study aims to analyze morphometric measurements and morphometric indices of female swamp buffalo aged 12–18 months in Bantarpanjang Village, Cibingbin District, Kuningan Regency. This study was conducted using a quantitative descriptive method with a census technique on the entire population of 11 female swamp buffalo aged 12–18 months. The morphometric parameters measured included shoulder height, body length, chest circumference, chest width, chest depth, hip height, and hip width. Data were analyzed using descriptive statistics to obtain the mean value, standard deviation, and coefficient of variation, then used to calculate the morphometric indices consisting of weight index, height slope index, length index, width slope index, depth index, and foreleg length. The results showed that the average shoulder height, body length, chest circumference, chest width, chest depth, hip height, and hip width were 93.82 cm, 83.36 cm, 121.55 cm, 28.00 cm, 47.65 cm, 98.05 cm, and 31.13 cm. The morphometric index values ​​obtained include a weight index of 285.68 kg, a height slope index of 0.04, a length index of 0.89, a width slope index of 1.12, a depth index of 0.51, and a foreleg length of 46.16 cm. In general, the morphometric size and morphometric index of female swamp buffalo in Bantarpanjang Village are still lower than the Indonesian National Standard (SNI) and research results in several other areas.